Dominance testing of transfers in Romania - Simler, Kenneth R.; Sahn, David E.; Younger, Stephen D. (Wiley, 2000)
In this paper we compare the progressivity of different government transfers made to households in Romania. We use distribution free standard errors to examine the difference between concentration curves that may be correlated, and thereafter employ statistical tests that take into account the covariance matrix for the ordinate estimates. In addition, we estimate extended Gini coefficients for the same transfers to check their consistency with the tests of inequality dominance. The results show that almost all transfer payments in Romania are progressive, and that they have an important effect on the distribution of income. Rankings among different transfer payments are, however, not robust. In particular, sensitivity analysis using different household equivalence scales indicates that many results are not consistent across scales, and that lower size elasticities contribute to changes in ranking of Ginis and loss of statistical significance in dominance tests.